Magnetic cooling - development of magnetic refrigerator - Tušek, Jaka (Strojniški vestnik, 2009)
The paper describes the development and design of a prototype rotary magnetic refrigerator (MR). The principle of the operation of the presented magnetic refrigerator is based on the rotary movement of active magnetic regenerators (AMRs) with magnetocaloric materials and on the stationary magnetic field generated by permanent magnets NdFeB. After a short description of the basics of magnetic refrigeration, this paper presents the development and analysis of the structure for generating the magnetic field and the basic operational principle of the first prototype magnetic refrigerator, which was developed at the Faculty of Mechanical Engineering. The second part of the paper provides a description of the development process for certain key elements of the complete magnetic refrigeration system.
Keywords: hlajenje; magnetno polje; magnetno hlajenje; permanentni magneti; hladilniki; gadolinij